2008
DOI: 10.1007/s00192-008-0702-z
|View full text |Cite
|
Sign up to set email alerts
|

A 5-year prospective follow-up study of vaginal surgery for pelvic organ prolapse

Abstract: The objective of this study was to evaluate anatomic, functional, short- and long-term outcome of vaginal surgery for pelvic organ prolapse. This was a prospective observational study of 185 consecutive women planned for vaginal prolapse reconstructive surgery. Stage of prolapse, urinary incontinence (UI), bowel and mechanical symptoms were assessed preoperatively and at 1, 3 and 5 years postoperatively. The mean follow-up time was 53 months. The anatomic recurrence rate was 41.1% but less than half of them we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
48
3
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(61 citation statements)
references
References 35 publications
5
48
3
2
Order By: Relevance
“…the one that is most likely to recur anatomically) is analysed separately, the re-operation rate is only 4.6% [13]. This has been seen in other studies with re-operation rates for the anterior compartment of between 5% and 10% at intervals between 1 and 5 years after a primary "traditional" procedure [14][15][16][17]. While these re-operation rates are not synonymous with failure, nonetheless, one would imagine that if after "failed" primary surgery the symptoms were bothersome then patients would seek further treatment, whether that be with vaginal pessaries or surgery.…”
Section: What Is the Evidence?mentioning
confidence: 65%
“…the one that is most likely to recur anatomically) is analysed separately, the re-operation rate is only 4.6% [13]. This has been seen in other studies with re-operation rates for the anterior compartment of between 5% and 10% at intervals between 1 and 5 years after a primary "traditional" procedure [14][15][16][17]. While these re-operation rates are not synonymous with failure, nonetheless, one would imagine that if after "failed" primary surgery the symptoms were bothersome then patients would seek further treatment, whether that be with vaginal pessaries or surgery.…”
Section: What Is the Evidence?mentioning
confidence: 65%
“…[1][2][3] Anatomical POP recurrence occurs in 40% of women in the operated compartment, with a re-operation rate of 9.7% due to symptomatic recurrence. 4 The main contributor for POP is vaginal delivery with damage to the levator ani muscle (LAM). 5,6 A recent review has shown that this damage, diagnosed on transperineal ultrasound (TPUS) a few months following childbirth, occurs in 13-36% of women.…”
Section: Introductionmentioning
confidence: 99%
“…On further analysis of the same compartment recurrence (i.e., repeat anterior repair), the reoperation rate was significantly lower, at 4.6% [12]. More recently, several investigators looked specifically at the issue of site-specific recurrence, with reoperation rates ranging from 2.8% to 9.7% [13][14][15]. A recent Cochrane review [16] looking at vault suspension suggested that reoperation rates after POP surgery, which includes suspension of the vaginal vault/apex, are 1.3% to 3.9% at 17 to 32 months respectively, depending upon the type of vault suspension.…”
Section: Introductionmentioning
confidence: 99%